Japanese Management for a Globalized World The Strength of the Lean, Trusting and Outward-Looking Firm - Watanabe, Satoko (Palgrave Macmillan Asian Business Series,, 2018)
This book provides a comprehensive analysis of the changes that have taken place in the systems and practices of Japanese management over the last quarter century, identifies the positive and useful attributes that ought to be maintained, and clarifies the behavioral principles that form the groundwork of their strengths. Observing the changes in the business environment brought about by the forces of intensifying globalization, the book presents a highly effective management model that builds on the superior aspects of Japanese-style management while overcoming its weaknesses. It is a multi-layered human-resources management model that combines the mutually complementary aspects of the Japanese and Anglo-Saxon systems, incorporating the strengths of both systems. This hybrid model is aimed at increasing workplace motivation, promoting the creation of new value, and enhancing performance and can be used successfully in many countries around the world. It will be of interest to business strategists and consultants, scholars, and entrepreneurs.